(untitled) (Dhaka Shishu (Children) Hospital Journal, 2020)
Background: Recently it has been apprehended that sildenafil, a drug which has been successfully using in the treatment of PPHN and erectile dysfunction in adult, is going to be withdrawn from the market of Bangladesh due to threat of its misuses. Objective: The aim of this study was to see the extent of uses of sildenafil in the treatment of PPHN and importance of availability of this drugs in the market inspite of its probable misuses. Methods: This cross sectional study was conducted in neonatal intensive care unit (NICU), special baby care unit (SCABU) and cardiac intensive care unit (CICU) of Dhaka Shishu (Children) Hospital from June, 2017 to May 2018. Neonates with PPHN were enrolled in the study. All cases were treated with oral sildenefil for PPHN along with others management according to hospital protocol. Data along with other parameters were collected and analyzed. Results: Total 320 patients with suspected PPHN were admitted during the study period. Among them 92 (29%) cases had PPHN. Male were 49(53 %) cases and female were 43(47%) cases. Mean age at hospital admission was 29.7±13.4 hours. Based on echocardiography,13(14%) cases had mild, 38 (41%) cases moderate and 41(45%) cases severe PPHN. Mean duration of sildenafil therapy was 11.9±7.1 days. Improved from PPHN were 83 (90%) cases. Mortality was 10% (9). Conclusion: In this study it was found that the incidence of PPHN is 29% among the suspected newborns. Sildenafil is successfull in improving the oxygenation of PPHN and to decrease the mortality of neonates. DS (Child) H J 2019; 35(2) : 100-104